Biocompatibility of a fish scale-derived artificial cornea: Cytotoxicity, cellular adhesion and phenotype, and in vivo immunogenicity. (March 2016) - van Essen, T.H.; van Zijl, L.; Possemiers, T.; Mulder, A.A.; Zwart, S.J.; Chou, C.-H.; Lin, C.C.; Lai, H.J.; Luyten, G.P.M.; Tassignon, M.J.; Zakaria, N.; El Ghalbzouri, A.; et al.
Abstract: Purpose: To determine whether a fish scale-derived collagen matrix (FSCM) meets the basic criteria to serve as an artificial cornea, as determined with in vitro and in vivo tests. Methods: Primary corneal epithelial and stromal cells were obtained from human donor corneas and used to examine the (in)direct cytotoxicity effects of the scaffold. Cytotoxicity was assessed by an MTT assay, while cellular proliferation, corneal cell phenotype and adhesion markers were assessed using an EdU-assay and immunofluorescence. For in vivo- testing, FSCMs were implanted subcutaneously in rats. Ologen ® Collagen Matrices were used as controls. A second implant was implanted as an immunological challenge. The FSCM was implanted in a corneal pocket of seven New Zealand White rabbits, and compared to sham surgery. Results: The FSCM was used as a scaffold to grow corneal epithelial and stromal cells, and displayed no cytotoxicity to these cells. Corneal epithelial cells displayed their normal phenotypical markers (CK3/12 and E-cadherin), as well as cell-matrix adhesion molecules: integrin-α6 and β4, laminin 332, and hemi-desmosomes. Corneal stromal cells similarly expressed adhesion molecules (integrin-α6 and β1). A subcutaneous implant of the FSCM in rats did not induce inflammation or sensitization; the response was comparable to the response against the Ologen ® Collagen Matrix. Implantation of the FSCM in a corneal stromal pocket in rabbits led to a transparent cornea, healthy epithelium, and, on histology, hardly any infiltrating immune cells. Conclusion: The FSCM allows excellent cell growth, is not immunogenic and is well-tolerated in the cornea, and thus meets the basic criteria to serve as a scaffold to reconstitute the cornea.